How Teachers are Dealing with Challenging Behaviour in Classroom - Gadour, Abdelbasit (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2013)
Generally education is concerned with development and growth and as such most of the teachers aim to offer the best nourishment to their pupils. However the aspirations of teachers are often hindered by disruptive incidents in their classes. This problem is particularly serious in Libya. Although the Libyan educational system appears to show somehow development, many aspects of the current educational situation can be disappointing. In line with this, primary school teachers are found to spend more time on managing behaviour than actually teaching. Thus, the aim of this study is to consider pupils misbehaviour within Libyan mainstream schools. The implication of this study underline the importance of strategies to deal with pupils’ misbehaviour.